Food insecure women's experiences of their nutritional health and wellbeing in Europe: a qualitative systematic review and meta-ethnography. (November 2022) - Bell, Zoë; Scott, Steph; Visram, Shelina; Rankin, Judith; Bambra, Clare; Heslehurst, Nicola
Abstract: Background: Food insecurity has increased since the 2008 global financial crisis. Particularly vulnerable are mothers with young children, pregnant women, and lone parents (the majority of whom are women). This systematic review and meta-ethnography of qualitative studies aimed to explore women's experiences of food insecurity and how it affects their nutritional health and wellbeing. Methods: Six electronic databases were searched from Jan 1, 2008, to July 10, 2021, with no language restrictions. Search terms included "food insecurity", "women", and "nutrition". This search was supplemented by grey literature, reference list, and citation searches. Screening was done in duplicate. Following title and abstract screening, full texts were screened against the inclusion criteria (ie, qualitative research, focus on women of childbearing age, pregnancy nutritional health or wellbeing, data from 2008 onwards, and high-income European countries). We adhered to PRISMA and eMERGe guidelines for meta-ethnographic reporting. Methodological quality was assessed using the CASP qualitative checklist. Data were synthesised according to Noblit and Hare's seven phases of meta-ethnography. Findings: We identified 11 589 unique records; 23 publications reporting data from 22 unique studies were included, comprising 647 women. We identified two key themes: accessing sufficient food and embodying food insecurity, comprising eight subthemes. Our meta-ethnography provides a progressive storyline of women's experiences of food insecurity. This storyline includes how women attempt to access sufficient food, they are unable to meet their nutritional needs, how this is embedded into their everyday lives, and embodied in unhealthful physical, social, and mental nutritional health and wellbeing. Interpretation: This meta-ethnography concludes a need for greater recognition of the psychosocial impact of food insecurity on vulnerable women, in addition to the impact on their nutritional health and wellbeing. The review demonstrates a lack of change over time, qualitatively for women's experiences. A strength and limitation of this review is the range of studies from different European contexts, where contextual factors could affect the experiences of women. Funding: The Economic and Social Research Council.